(3LQGH GdeLQHGJ hNRGfI GdCWHGAs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPG cJGH JNjQJg ef cJH GdCWHGA , hCdbjJ ajg eG hLOJg ef GdeLQHGJ ,hCdaJg HdaX eNJUQ s
(3BNQgG (B:s
(3jSJYed efg Ydi GdQjb eYdbI HeGA HGQO , ajTai s
(3QJHg Ydi JSY hYTQjf HGHkGs
(3fSNI ZjQ eDQNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B62 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(1196(1)) s
Keywords: (3GdWHs